The risk of divorce and household saving behavior - Libertad González; Berkay Özcan (Institute for the Study of Labor (IZA), 2008)
We analyze the impact of an increase in the risk of divorce on the saving behaviour of married couples. From a theoretical perspective, the expected sign of the effect is ambiguous. We take advantage of the legalization of divorce in Ireland in 1996 as an exogenous increase in the likelihood of marital dissolution. We analyze the saving behaviour over time of couples who were married before the law was passed. We propose a difference-in-differences approach where we use as comparison groups either married couples in other European countries (not affected by the law change), or Irish families who did not experience a significant increase in the expected risk of divorce (such as very religious families, or single individuals). Our results suggest that the increase in the risk of divorce brought about by the law was followed by an increase in the propensity to save of married couples, consistent with a rise in precautionary savings interpretation. An increase in the risk of marital dissolution of about 40 percent led to a 7 to 13 percent rise in the proportion of married couples reporting positive savings.
urn:nbn:de:101:1-20081014319
Keywords: J12; 330; Divorce; saving; marriage; divorce law; Scheidung; Risiko; Sparen; Privater Haushalt; Familienökonomik; Eherecht; Irland